Reducción de contaminantes (CROMO, DBO, DGO) por electrolisis en las curtiembres de la Provincia de Tungurahua - Morales Villacís, Adriana Belén (2023)
In the Ecuadorian territory, the leather industry has a relevant trajectory in the development of the tanning sector, therefore, the objective of this work is focused on the reduction of pollutants produced by tanneries such as chrome, Biochemical Oxygen Demand at 5 days (BOD5) and Chemical Oxygen Demand (COD), by means of electrolysis (separation of an element with the help of electricity), 4 samples are considered, with 3 variables: amperes (amount of electrical energy), distance and time due because they are very important factors for the reduction of pollutants. In the tests carried out with the different variables, a minimum decrease of 50% in the concentration of pollutants is evident, however the second sample is the one that decreased the most amount of BOD5, COD and total chromium, 10 amps was used as variables, distance of 30 centimeters and an electrolysis time of 24 hours, which concludes that the greater the electrolysis distance, the chromium contaminants decrease because the electromagnetic field is weakened by the separation of the electrodes; by reducing chromium there is a decrease in other parameters such as BOD5 and COD.